Wizerunek Jana Pawła II w kulturze współczesnej: "odjaniepawlenie" i "dewojtylizacja" w literaturze i w najnowszych filmach = The image of John Paul II in the contemporary culture: de-johnpaulization and de-wojtylization in the latest literature and movies - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Considering statements presented in literature and in the media, as well as dictionary definitions on the Internet, the author of this paper discusses and (re)defines new phenomena related to John Paul II, which include: papaphilia, "janopawlenie" ("johnpauling"), "odjanopawlenie" ("de-johnpaulization"), wojtylianism, "dewojtylizacja" ("de-wojtylization"), "rewojtylizacja" ("re-wojtylization"). She scrutinizes the emergence of those phenomena in literature (especially Polish) and in movies (Polish and foreign), and also investigates their meaning, noticing that they are equivocal, also axiologically.
Keywords: Jan Paweł II, papież (1929-2005); film; literatura; dewojtylizacja; odjaniepawlenie; papafilia; John Paul II; literature; de-wojtylization; de-johnpaulization; papaphilia